Universitat, llengua i societat a les Illes Balears - Bibiloni, Gabriel (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: A critical study on the use of Catalan at the University of Palma and on the results of a social-linguistic survey in Mallorca, which shows the compatibility of the spanishisation process an increasing prestige of Catalan.